Estimating age and growth parameters for three commercial NE-Atlantic sea cucumbers, Holothuria mammata, H. forskali and H. arguinensis, in a marine protected area - Azevedo e Silva, Francisco; Brito, Ana C.; Simões, Tomás; Pombo, Ana; Sousa, João; Venâncio, Eliana; Félix, Pedro M. (Frontiers in Marine Science, 2024)
Sea cucumbers, integral components of benthic ecosystems, have become subjects of scientific scrutiny owing to their intricate morphology and ecological importance. Due to increasing demand, several species of these echinoderms have become overexploited. As a consequence, NE-Atlantic species became new targets for the international markets. There is a vital need for comprehensive biological data to establish and enhance holothurian fisheries management. In the absence of such data, there is a risk of ineffective fisheries regulations, particularly for susceptible commercial species in the NE-Atlantic, which could lead to overexploitation. Establishing effective fisheries regulations requires a foundation of fundamental biological information, such as growth rates from target populations. This work aims to determine the growth parameters for three commercial sea cucumber species from the NE-Atlantic, in a marine protected area, Holothuria mammata, H. forskali and H. arguinensis. This presents a challenge, as sea cucumbers lack significant calcified structures for age determination, and assessing size is complicated because of their body size plasticity. Thus, a von Bertalanffy model was fitted to length-frequency data using the ELEFAN method with the simulated annealing procedure. Underwater length measurements of the three sea cucumber species, in a relaxed state, were systematically recorded over a span of 18 months, with measurements taken every 1.5 months. The results provide the growth parameters of each species. Models considering seasonal growth were better fits to the data. The three species had different growth rates and periods of no growth coincided with the reproductive season. Mortality was lower for the species growing slower. This is crucial information to support decision-making processes regarding stock management, such as setting limits to fisheries considering stock condition associated with environmental variability.